Encapsulation of hydrophobic vitamins by polylactide stereocomplexation and their release study. Issue 11 (12th August 2018) - Wojtczak, Edyta; Gadzinowski, Mariusz; Makowski, Tomasz; Maresz, Katarzyna; Kubisa, Przemysław; Bednarek, Melania; Pluta, Mirosław
ABSTRACT: Among different drug‐containing formulations prepared from biodegradable polymers, those based on polylactide (PLA) (usually block copolymers with poly(ethylene glycol)) are the most frequently developed and improved. A new easy method of such drug delivery system preparation with the application of PLA stereocomplexation is presented. The encapsulation of hydrophobic vitamins such as D3, E and A by spontaneous precipitation of microparticles with an average diameter of 1–2 µm led to a loading of about 10 wt% and an encapsulation efficiency in the range 27%–45% when a vitamin:PLA weight ratio of 3:10 was applied. SEM, TEM, X‐ray photoelectron spectroscopy and nitrogen absorption analysis of neat and vitamin‐loaded microparticles indicate a porous structure of the microparticles and confirm the presence of vitamins inside with an enriched surface layer. The release of vitamins into a phosphate buffer (pH 7.4) at 37 °C takes place at a low rate according to almost zero‐order kinetics (35%–60% of vitamin over 4 weeks). © 2018 Society of Chemical Industry Abstract : A new easy method of preparation of drug delivery systems based on polylactide with the application of polylactide stereocomplexation is presented. Microspheres containing hydrophobic vitamins and calcium ions were prepared and analyzed.